Edentulism in the elderly in Montenegro - Popović Zorica (Serbian Medical Society - Dental Section, Belgrade, 2020)
Introduction For the first time in Montenegro, a survey was conducted to examine the oral health status of the elderly. Materials and methods The study included 170 subjects of both genders, average age 72.32 ± 6.85 years. The research methodology was in line with the WHO methodological guidelines for epidemiological studies of national oral pathology. For statistical analysis of data IBM STATISTICS 20 was used. Descriptive and inferential statistical methods, Tamhane T2 post hoc tests, ch2 test were applied. The homogeneity of the dispersions was checked by the Leven test. The significance level was set to 0.05. Results The DMFT value was 29.417 ± 3.81 (MT: 26.25 ± 6.95; FT: 2.68 ± 3.98; DT: 0.63 ± 1.56) and it was significantly higher in women, smokers and people who did not visit the dentist regularly. The percentage of edentulous persons was 46.47%. The index of dental rehabilitation - IRD was 73.86%. The average age of dentures was 11 years. Conclusion The state of oral health of the elderly in Montenegro is not at satisfactory level, which is reflected in the high percentage of edentulous people and unfavorable structure of DMFT.